2021
DOI: 10.1007/s40744-021-00407-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Manifestations in Rheumatoid Arthritis vs. Spondyloarthritis: A Systematic Literature Review

Abstract: Introduction: Misclassification of spondyloarthritis (SpA) as rheumatoid arthritis (RA) may lead to delayed SpA diagnosis and suboptimal therapeutic outcomes. Here, we evaluate the literature on clinical manifestations in patients with SpA and RA, particularly seronegative RA, to understand the potential overlap, distinctions, and most reliable approaches to accurate diagnosis. Methods: In this systematic literature review, conducted according to PRISMA guidelines, we searched key biomedical databases for Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 87 publications
0
9
0
6
Order By: Relevance
“…Because of the continuous destruction of joints, early diagnosis and treatment are particularly important [ 13 ]. However, the clinical manifestations of early diseases are similar, the diagnosis time is too long, and there is no effective biomarker, especially the negative serum rheumatoid factor and anti-cyclic citrulline antibody, which bring great difficulties to the treatment [ 14 ]. Increasing number of studies have shown that the inflammatory microenvironment and inflammatory cells of synovium play an indispensable role in diseases [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the continuous destruction of joints, early diagnosis and treatment are particularly important [ 13 ]. However, the clinical manifestations of early diseases are similar, the diagnosis time is too long, and there is no effective biomarker, especially the negative serum rheumatoid factor and anti-cyclic citrulline antibody, which bring great difficulties to the treatment [ 14 ]. Increasing number of studies have shown that the inflammatory microenvironment and inflammatory cells of synovium play an indispensable role in diseases [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Во-вторых, диагностика серонегативного РА, основанная на классификационных (а не диагностических) критериях, может быть затруднена, особенно на ранних стадиях заболевания [17]. Диагноз нередко верифицируется только в процессе длительного наблюдения пациентов [18][19][20]. Это затрудняет своевременное назначение адекватной противовоспалительной терапии в рамках стратегии «лечение до достижения цели» (treat-to-target) [21].…”
Section: Introductionunclassified
“… 1 , 2 Clinically, RA not only causes swollen and tender joints, but also affects other systems or organs apart from the joints including skin, eyes, cardiovascular system, neuron system, etc. 3 Fortunately, with the induction of tumor necrosis factor (TNF) inhibitors, the most commonly used biologics, the treatment approaches of RA have been greatly enriched. 4 , 5 , 6 For RA patients who may not respond to conventional disease‐modifying anti‐rheumatoid drugs (cDMARDs), using TNF inhibitors is a promising option; meanwhile, it is also reported that using TNF inhibitors as the first‐line therapy is a cost‐effective strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an autoimmune disease that affects approximately 1% of the entire human beings with the incidence ranging from 8 to 45 per 100,000 populations per year 1,2 . Clinically, RA not only causes swollen and tender joints, but also affects other systems or organs apart from the joints including skin, eyes, cardiovascular system, neuron system, etc 3 . Fortunately, with the induction of tumor necrosis factor (TNF) inhibitors, the most commonly used biologics, the treatment approaches of RA have been greatly enriched 4–6 .…”
Section: Introductionmentioning
confidence: 99%